Relacje amerykańsko-afgańskie w latach 1963-1978 = US-Afghan relations in the years 1963-1978 - Jureńczyk, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article raises the issue of the relationship between the United States and Afghanistan in the years 1963-1978. The subject of the analysis are political and economic relations between the partners. The author points out the motivations of American and Afghan authorities and barriers to collaboration. They are shown on the background of internal events in Afghanistan and the international context, including the global rivalry between the United States and the Soviet Union.
Keywords: Stany Zjednoczone Ameryki Północnej - a Afganistan; Afganistan - a Stany Zjednoczone Ameryki Północnej; historia - 1945-1989